Ultraviolet absorption enhanced aggregation-induced emission (AIE) polymer and application thereof in sunlight catalysis
By introducing ultraviolet absorbers into the polymer chain of HPCB, HPCB-UV materials were synthesized, solving the problems of insufficient absorption and insufficient intelligent response of photocatalytic materials in the ultraviolet light region, and realizing the integration of efficient full-spectrum photocatalysis and information encryption.
Patent Information
- Application Number
- CN202511805758.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-03
- Publication Date
- 2026-01-27
AI Technical Summary
Existing photocatalytic materials have insufficient absorption in the ultraviolet region and lack intelligent acid-base response characteristics, making it difficult to achieve the integration of full-spectrum photocatalysis and information encryption.
By introducing a UV absorber into the polymer chain end of HPCB, a UV-enhanced polymer HPCB-UV was synthesized, which possesses aggregation-induced emission (AIE) properties and reversible acid-base response characteristics, thereby enhancing its photocatalytic performance in the UV and visible light regions.
It significantly improves the absorbance of photocatalytic materials in the ultraviolet band, achieves efficient full-spectrum photocatalytic performance, and realizes reversible control of optical properties through acid-base response characteristics, making it suitable for information encryption and solar photocatalysis.
Smart Images

Figure CN121405928A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional polymers and photocatalytic materials technology, and relates to a method for synthesizing novel photocatalytic polymers with enhanced ultraviolet absorption through chain-end chemical modification. Specifically, this invention relates to a method for regulating the optical properties of the polymer HPCB-UV based on its acid-base responsiveness, and its application in photocatalytic hydrogen production. Background Technology
[0002] Acid-base responsive materials can achieve functional regulation through pH changes, but existing materials generally suffer from problems such as complex synthesis, insignificant response, and poor reversibility. Developing novel acid-base responsive materials with significant optical changes, high reversibility, and simple synthesis is of great significance for promoting their application in high-end fields such as dynamic anti-counterfeiting and microenvironment monitoring.
[0003] Utilizing solar photocatalysis to convert light energy into chemical energy (such as photocatalytic hydrogen production) is a crucial approach to solving energy and environmental problems. The solar spectrum primarily consists of ultraviolet (approximately 5%), visible (approximately 43%), and infrared (approximately 52%) light. Currently, most research focuses on developing visible-light-responsive catalysts to fully utilize the most abundant visible portion of sunlight. However, ultraviolet photons in sunlight have significantly higher energy than visible light, offering unique advantages in driving photocatalytic reactions, particularly in stimulating wide-bandgap active centers. Therefore, developing full-spectrum photocatalytic materials capable of synergistically utilizing both ultraviolet and visible light is essential for maximizing solar energy conversion efficiency.
[0004] On the other hand, stimulus-responsive smart materials have attracted much attention in the fields of information encryption and sensing. Among them, acid-base stimuli-responsive materials can produce reversible, visible optical changes (such as color or fluorescence) based on the ambient pH value, providing a simple and efficient tool for dynamic anti-counterfeiting and chemical sensing. Currently, reports integrating broadband photocatalytic functions with intelligent acid-base responsive properties into a single molecular system are still relatively rare.
[0005] Therefore, there is an urgent need in this field for a new material that can not only break through the absorption limitations of traditional catalysts in the ultraviolet region to achieve efficient full-spectrum photocatalysis, but also possess sensitive acid-base response intelligence, thus providing a new solution for developing multifunctional materials that integrate energy conversion and information encryption. Summary of the Invention
[0006] The purpose of this invention is to provide a polymer HPCB-UV with enhanced ultraviolet absorption capacity through chemical modification, and to disclose its newly discovered acid-base response characteristics. Based on this, a novel material with both intelligent response characteristics and efficient full-spectrum photocatalytic activity is developed to solve the problems of insufficient ultraviolet light utilization and lack of intelligent control capability in existing photocatalytic materials.
[0007] On one hand, this invention provides a method for synthesizing a fluorescent polymer material with strong ultraviolet absorption, HPCB-UV, through chemical modification of HPCB. This polymer exhibits aggregation-induced emission (AIE) and reversible acid-base response properties, and its reaction equation is as follows:
[0008] The method for synthesizing a UV-enhanced polymer (HPCB-UV) is characterized in that: the Br atom at the chain end of the HPCB polymer is replaced by a benzophenone-based UV absorber selected from oxybenzophenone, 2,4-dihydroxybenzophenone, etc., through nucleophilic substitution, thereby synthesizing the UV-enhanced polymer (HPCB-UV).
[0009] Furthermore, the ultraviolet absorption-enhanced polymer is a fluorescent polymer with aggregation-induced emission (AIE) properties, exhibiting weak fluorescence in solution and strong luminescence intensity in aggregated state.
[0010] On the other hand, the present invention discovered that the polymer HPCB-UV has reversible acid-base response characteristics. In the solution state, its color changes from yellow to orange-red as the pH decreases, and in the aggregated state, its color changes from yellow to orange-red and its fluorescence is quenched.
[0011] Furthermore, the present invention also provides a method for preparing the above-mentioned ultraviolet absorption-enhanced polymer, specifically including the following preparation process: Step 1: In a Schlenk tube containing Cs₂CO₃, add curcumin and 1,3-di(bromomethyl)benzene, and dissolve them in THF. Place the mixture in air at 70°C and stir slowly for 12 hours.
[0012] Step 2: After stirring the reaction for 12 hours, add oxybenzone to the mixed solution and place the mixed solution in air at 70°C and continue stirring for 12 hours.
[0013] Step 3: After 12 hours, allow the reaction solution to cool to room temperature. Filter the Cs₂CO₃ from the mixture and concentrate the mixture under reduced pressure. Precipitate the product in excess petroleum ether, filter, and vacuum dry to obtain a yellow solid powder, i.e., the HPCB-UV polymer.
[0014] Furthermore, the absorbance of the polymer in the 200-400 nm ultraviolet band is significantly improved compared to HPCB, and under AM 1.5 simulated full-spectrum sunlight irradiation, its photocatalytic hydrogen production rate is 882 µmol g higher than that of HPCB. −1 h −1 .
[0015] Furthermore, the ultraviolet absorption enhanced polymer HPCB-UV has reversible acid-base responsive aggregation-induced emission (AIE) properties. The optical properties of this polymer change under specific pH conditions, that is, its ultraviolet-visible absorption spectrum undergoes reversible intensity changes with pH value.
[0016] Furthermore, by adding alkali to the aggregation system of the UV absorption-enhanced polymer HPCB-UV for pH adjustment, the polymer color changed from yellow to orange-red under sunlight with the addition of alkali, and the yellow fluorescence under UV irradiation was significantly quenched; with the addition of acid, the polymer color under sunlight returned from orange-red to yellow, and the yellow fluorescence emission intensity gradually increased.
[0017] Furthermore, by adding alkali to the HPCB-UV solution of the UV absorption-enhanced polymer for pH adjustment, a significant color change from pale yellow to orange-red can be observed under sunlight with the addition of alkali, while the intensity of the characteristic absorption peak in the 450-600 nm range of its UV-Vis absorption spectrum gradually increases; with the addition of acid, the color of the system can be observed to return from orange-red to pale yellow under sunlight, and the intensity of the characteristic absorption peak in the 450-600 nm range of its UV-Vis absorption spectrum gradually decreases.
[0018] The present invention provides a UV absorption-enhanced polymer HPCB-UV prepared by the above-described synthesis method.
[0019] The ultraviolet absorption enhanced polymer HPCB-UV, prepared by the above-described synthesis method of the present invention, is characterized in that it is applied in screen printing to encrypt text by utilizing its acid-base stimulation response characteristics.
[0020] The ultraviolet absorption enhanced polymer HPCB-UV prepared by the above-described synthesis method of the present invention is characterized in that: when applied to the field of solar photocatalysis, it can enhance the catalytic performance of catalytic materials in the ultraviolet and visible light range of sunlight.
[0021] Compared with the prior art, the present invention has the following advantages and effects: The acid-base response characteristics of HPCB-UV have been discovered: This invention reveals and utilizes its unique acid-base response for the first time, realizing the reversible control of its optical properties by the ambient pH value, and providing a new approach for the development of smart responsive photocatalytic materials.
[0022] Enhanced UV absorption at the molecular level was achieved: UV-absorbing groups were introduced at the ends of HPCB molecular chains through nucleophilic substitution, forming a well-defined polymer with strong UV absorption, which effectively solved the problems of poor interfacial contact and easy separation of components in physical blending.
[0023] The modified polymer exhibits a significantly enhanced full-spectrum photocatalytic efficiency. Its absorbance in the 200-400 nm ultraviolet band is significantly increased. Under full-spectrum AM 1.5G simulated sunlight irradiation, 20%HPCB-UV-Pt-TiO2 demonstrates superior photocatalytic performance, achieving a hydrogen production rate of 4330 µmol g⁻¹ h⁻¹, which is 882 µmol g⁻¹ higher than that of 20%HPCB-Pt-TiO2. −1 h −1 . Attached Figure Description
[0024] Figure 1 This is a digital photograph of the acid-base stimulation response of polymer HPCB-UV in the aggregated state of a specific embodiment of the present invention; the first 20 seconds in the figure are fumigation with concentrated ammonia water, followed by fumigation with concentrated hydrochloric acid for 20 seconds.
[0025] Figure 2 This is a digital photograph and ultraviolet-visible absorption spectrum of the acid-base stimulation response of polymer HPCB-UV solution in a specific embodiment of the present invention.
[0026] Figure 3 This is a digital photograph with text encryption achieved through screen printing, as described in Specific Embodiment 3 of the present invention.
[0027] Figure 4 The figures show the fluorescence performance characterized in Example 4 of this invention; in the figures: a is the excitation and emission spectra of HPCB-UV powder; b is the CIE coordinates of HPCB-UV powder; c is the addition of a drop of HPCB-UV solution to a TLC plate by dissolving HPCB-UV in THF and using a capillary tube. As the solvent gradually evaporates from the TLC plate, HPCB-UV gradually accumulates from the THF solution, and the luminescence intensity on the TLC plate increases accordingly, thus confirming its AIE behavior; d is the emission spectrum of HPCB-UV THF solution at different water contents; e is the trend of optimal emission intensity of HPCB-UV THF solution at different water contents; f is a digital photograph of HPCB-UV THF solution at different water contents.
[0028] Figure 5 This is a comparison of the ultraviolet absorption spectra of the product obtained in Example 1 of the present invention with those of HPCB and oxybenzone.
[0029] Figure 6 This is a comparison graph showing the photocatalytic rate of the product obtained in Example 5 of the present invention under simulated sunlight (AM1.5) and the photocatalytic rate of HPCB. Detailed Implementation
[0030] The following provides a detailed description of the present invention with accompanying drawings and specific embodiments. The following specific embodiments are only used to explain the present invention, and the scope of protection is not limited by the following embodiments.
[0031] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0032] The experimental data in the examples were measured using the following instruments and methods: (1) Method for determining the ultraviolet absorption of the generated polymer: The ultraviolet absorption was determined by ultraviolet spectrophotometer; (2) Method for determining the fluorescence properties of the generated polymer: fluorescence spectrometer was used.
[0033] Example 1 Preparation of UV-absorbing enhanced polymers: Step 1: In a Schlenk tube containing Cs₂CO₃ (1.3 g, 3 eq), add curcumin (0.5 g, 1 eq) and 1,3-di(bromomethyl)benzene (0.9 g, 2.5 eq), and dissolve in 7 mL of THF. Place the mixture in air at 70 °C and stir slowly for 12 h.
[0034] Step 2: After stirring the reaction for 12 hours, add oxybenzone (0.3 g, 1 eq) to the mixed solution and continue stirring in the air at 70°C for 12 hours.
[0035] Step 3: After 12 hours, allow the reaction solution to cool to room temperature. Filter out the Cs₂CO₃ from the reaction solution and concentrate the solution under reduced pressure. Precipitate the obtained product in excess petroleum ether, filter, and vacuum dry to obtain a yellow solid powder, i.e., HPCB-UV.
[0036] Example 2 Determination of the acid-base response of HPCB-UV.
[0037] 10 mg of the polymer HPCB-UV prepared in Example 1 was dissolved in 1 mL of THF. The solution was then applied to a TLC plate using a capillary tube. After the solvent evaporated, the TLC plate was placed above concentrated ammonia. As the concentrated ammonia evaporated, the pH value on the TLC plate surface gradually increased, and the color of HPCB-UV under sunlight gradually changed from yellow to orange-red, while the fluorescence intensity gradually decreased. Subsequently, the TLC plate was placed on concentrated hydrochloric acid. As the concentrated hydrochloric acid evaporated, the pH value on the TLC surface gradually decreased, and the color of HPCB-UV under sunlight gradually returned from orange-red to yellow, while the fluorescence intensity gradually recovered. (See figure). Figure 1 .
[0038] A 0.1 mg / mL HPCB-UV THF solution was prepared. The HPCB-UV solution was then subjected to UV-UV acid-base titration with 1 mol / L NaOH solution. As the pH value gradually increased, the solution color gradually changed from pale yellow to orange-red, and the intensity of the characteristic absorption peak in the 450-600 nm range of its UV-Vis absorption spectrum gradually increased. With the addition of acid, the pH value gradually decreased. Under sunlight, the system's color was observed to return from orange-red to pale yellow, and the intensity of the characteristic absorption peak in the 450-600 nm range of its UV-Vis absorption spectrum gradually decreased. (See...) Figure 2 .
[0039] Example 3 The polymer HPCB-UV solution prepared in Example 1 at a concentration of 1 g / mL was used as the dye. Screen printing was performed by placing the solution on a yellow background to hide the image, and then placing it on concentrated ammonia. As the pH value of the polymer surface increased, the color changed from yellow to orange-red, and the pattern gradually appeared. Figure 3 .
[0040] Example 4 The solid-state fluorescence spectrum of the polymer prepared in Example 1 was measured, see... Figure 4 .
[0041] The polymer prepared in Example 1 exhibited aggregation-induced emission in THF / water mixed solutions with different volume ratios, see [link to example]. Figure 4 .Depend on Figure 4 It is known that in mixed solutions of different THF / water volume ratios, as the content of undesirable solvent (water) increases, the polymer gradually precipitates out and forms nano-aggregates. As the degree of aggregation increases, the fluorescence gradually increases, showing an obvious aggregation-induced emission effect.
[0042] 5 mg of the polymer prepared in Example 1 was dissolved in 1 mL of THF. The solution was then spotted onto a TCL plate using a capillary tube. As the solvent on the plate gradually evaporated, the polymer gradually aggregated, and the fluorescence intensity on the TCL plate increased accordingly. Figure 4 As shown.
[0043] The UV absorption spectrum (test wavelength 500 nm) of the polymer prepared in Example 1 was tested in a 0.01 mg / mL THF solution. The results showed that the absorbance of HPCB-UV in the 200-400 nm UV band was significantly improved compared to HPCB. Figure 5 As shown.
[0044] Example 5 Preparation of Pt-20%HPCB-UV-TiO2 Step 1: Tetraisopropyl titanate was hydrolyzed under acidic conditions to pH = 4 to obtain TiO2 sol. Subsequently, a gel was obtained by microwave dehydration. The resulting gel was transferred to an alumina crucible, placed in a muffle furnace, and heated to 300 °C at a programmed heating rate of 5 °C / min. The mixture was then calcined at this temperature for 5 hours to obtain pure-phase TiO2 powder.
[0045] Step 2: Weigh 20 mg of HPCB-UV and 100 mg of TiO2 powder prepared in Step 1. Dissolve HPCB-UV in 10 mL of dichloromethane, then add the TiO2 powder. Stir the mixture continuously for 1 hour to ensure sufficient contact. After the reaction is complete, centrifuge to collect the solid, and wash it five times with dichloromethane to remove the physically adsorbed HPCB-UV molecules on the surface. Finally, dry the solid product at 60 °C for 2 hours to obtain a 20% HPCB-UV-TiO2 composite material.
[0046] Step 3: Accurately weigh 50 mg of the 20%HPCB-UV-TiO2 composite material prepared in Step 2 and place it in a quartz reactor. Add 4 mL of deionized water, 4 mL of methanol, and 66.5 μL of chloroplatinic acid aqueous solution (10 mg / mL) sequentially. Purge the reaction system with nitrogen for 10 minutes to remove air, then irradiate with ultraviolet light for 1 hour with stirring. After the reaction is complete, collect the solid product by centrifugation, wash three times with deionized water, and finally dry under vacuum at 60 °C for 12 hours to obtain the target catalyst Pt-20%HPCB-UV-TiO2.
[0047] To evaluate the photocatalytic performance of the prepared samples, H2 evolution experiments were conducted under AM 1.5G simulated full-spectrum sunlight irradiation using triethanolamine (TEOA) as a sacrificial agent and platinum (Pt) as a co-catalyst. The experimental results are shown in [Figure number missing]. Figure 6 20%HPCB-UV-Pt-TiO2 exhibited superior photocatalytic performance, with a hydrogen production rate of 4330 µmol g⁻¹ h⁻¹, which is 882 µmol g⁻¹ higher than that of 20%HPCB-Pt-TiO2. −1 h −1 (The photocatalytic hydrogen production rate described in the corresponding invention description is 882 µmol g higher than that of HPCB) −1 h −1 ).
Claims
1. A method for synthesizing a high-violet-absorbing polymer (HPCB-UV), characterized in that: By replacing the Br atom at the chain end of the HPCB polymer with a benzophenone-based UV absorber selected from oxybenzophenone, 2,4-dihydroxybenzophenone, etc., through nucleophilic substitution, a UV absorption-enhanced polymer (HPCB-UV) is synthesized.
2. The method for synthesizing the ultraviolet absorption enhanced polymer HPCB-UV according to claim 1, characterized in that: The ultraviolet absorption-enhanced polymer is a fluorescent polymer with aggregation-induced emission (AIE) properties. It exhibits weak fluorescence in solution and strong luminescence intensity in aggregated state.
3. The method for synthesizing the ultraviolet absorption enhanced polymer HPCB-UV according to claim 1, characterized in that: Specifically, the steps include the following: Step 1: In a Schlenk tube containing Cs2CO3, add curcumin and 1,3-di(bromomethyl)benzene and dissolve them in THF. Place the resulting mixed solution in air at 70°C and stir slowly for 12 hours. Step 2: After stirring the reaction in Step 1 for 12 hours, add a benzophenone-based ultraviolet absorber selected from oxybenzone and 2,4-dihydroxybenzophenone to the mixed solution, and continue stirring the mixed solution in air at 70°C for 12 hours. Step 3: After stirring the mixed solution from Step 2 in air at 70°C for 12 hours, and then cooling the reaction solution to room temperature, filter out the Cs2CO3 in the reaction solution, concentrate the reaction solution under reduced pressure, precipitate the obtained product in excess petroleum ether, filter and vacuum dry to obtain a yellow solid powder, which is the HPCB-UV polymer.
4. The method for synthesizing the ultraviolet absorption enhanced polymer HPCB-UV according to claim 1, characterized in that: The UV absorption-enhanced polymer HPCB-UV exhibits significantly improved absorbance in the 200-400 nm UV band compared to HPCB, and under AM 1.5G simulated full-spectrum sunlight irradiation, its photocatalytic hydrogen production rate is 882 µmol g higher than that of HPCB. −1 h −1 .
5. The method for synthesizing the ultraviolet absorption enhanced polymer HPCB-UV according to claim 1, characterized in that: The ultraviolet absorption-enhanced polymer HPCB-UV has reversible acid-base responsive aggregation-induced emission (AIE) properties. The optical properties of this polymer change under specific pH conditions, that is, its ultraviolet-visible absorption spectrum undergoes reversible intensity changes with pH value.
6. The method for synthesizing the ultraviolet absorption enhanced polymer HPCB-UV according to claim 1, characterized in that: By adding alkali to the aggregation system of the UV absorption-enhanced polymer HPCB-UV for pH adjustment, the polymer's color changes from yellow to orange-red under sunlight with the addition of alkali, and the yellow fluorescence is significantly quenched under UV irradiation; with the addition of acid, the polymer's color under sunlight returns from orange-red to yellow, and the yellow fluorescence emission intensity gradually increases.
7. The method for synthesizing the ultraviolet absorption enhanced polymer HPCB-UV according to claim 1, characterized in that: By adding alkali to the HPCB-UV solution of the UV absorption-enhanced polymer for pH adjustment, a significant color change from pale yellow to orange-red can be observed under sunlight as alkali is added, while the intensity of the characteristic absorption peak in the 450-600 nm range of its UV-Vis absorption spectrum gradually increases. With the addition of acid, the color of the system can be observed to return from orange-red to pale yellow under sunlight, and the intensity of the characteristic absorption peak in the 450-600 nm range of its UV-Vis absorption spectrum gradually decreases.
8. An ultraviolet absorption enhanced polymer HPCB-UV prepared by the synthesis method according to any one of claims 1-7.
9. A UV-absorbing enhanced polymer HPCB-UV prepared by any one of the synthesis methods described in claims 1-7, characterized in that: It is used in screen printing to encrypt text by utilizing its acid-base stimulation response characteristics.
10. A UV-absorbing enhanced polymer HPCB-UV prepared by any one of the synthesis methods described in claims 1-7, characterized in that: When applied to the field of solar photocatalysis, it can enhance the catalytic performance of catalytic materials in the ultraviolet and visible light range of sunlight.